A Framework For Effective Formal Mentoring Of Novice Teachers - Mphojane, Morakane, Constance. (Central University of Technology, Free State, 2019)
The aim of this phenomenological qualitative study was to develop a framework for the formal mentoring of novice teachers. To achieve this aim, the study successfully responded to research questions, which sought to find the mentoring essences, practices, barriers, benefits and specific needs of novice teachers. Veterans and novice teachers were purposefully selected from eight English-medium secondary schools in the Lejweleputswa Education District in the Free State province of South Africa. Veterans are considered to be teachers with more than three years’ experience in teaching while novices are those with two years or less. Data from the literature review, focus group interviews and open-ended questionnaires were triangulated and thematically analysed to gain a deeper understanding of the phenomenon. Veterans and novice teachers gave their life experiences, perspectives and perceptions on formal mentoring. The study revealed that in South African schools, mentoring is patchy and unsystematic. Data collected revealed a new working environment presents some social, personal and professional challenges to novices. It revealed that veteran teachers were willing to support their fellow novice colleagues despite the fact they were not trained and did not receive the necessary support from the School Management Team (SMT). It revealed practices and barriers that usually contributed to the premature exit of novice teachers from the profession. The study also identified the benefits of a formal mentoring programme, which were collaborative, transformative and focusing on the specific needs of novices. Findings of this study were used to develop a framework for an effective formal mentoring programme, which aims at the socialisation, personal and professional enhancement of novice teachers in order to increase self-efficacy, job satisfaction, performance and retention. The framework outlined staff members, veterans, novices, support teams, development needs and accountability as the main components. There should be training of mentors, needs assessments, collaboration and formulation of mentoring programme objectives in order to provide effective mentoring to novice teachers.
Thesis
Keywords: Development Needs; Essences of Mentoring; Formal Mentoring; Mentees; Mentoring Practices; Mentoring Programme; Mentoring Relations; Mentors; Novice Teachers; Veteran Teachers